Penyelesaian Sengketa Hasil Pemilihan Kepala Daerah dan Prinsip Keadilan Konstitusional: Analisis Putusan Mahkamah Konstitusi Nomor 152/PHPU.BUP-XXIII/2025 dalam Perspektif Demokrasi dan Nilai Islam - Koko Nugroho; Halimatul Maryani (Albayan Journal of Islam and Muslim Societies, 2025)
This article examines the settlement of regional head election disputes in Indonesia through an analysis of Constitutional Court Decision No. 152/PHPU.BUP-XXIII/2025 concerning the 2024 Regent Election of Deli Serdang. The study aims to assess how the Constitutional Court resolves electoral disputes within the framework of constitutional justice and to evaluate the decision from the perspective of electoral justice and Islamic values relevant to Muslim societies. Employing a qualitative normative–empirical legal research approach, this article analyzes constitutional provisions, statutory regulations, and the Court’s legal reasoning (ratio decidendi), supported by limited empirical data related to the electoral context.  The findings indicate that the Constitutional Court consistently prioritizes procedural justice by strictly applying the vote-difference threshold as stipulated in Law No. 10 of 2016, thereby emphasizing legal certainty and political stability. However, this procedural orientation potentially constrains substantive justice, particularly when claims relate to the quality of the electoral process and voter participation affected by external conditions. From the perspective of Islamic legal and ethical principles—such as ʿadl (justice), amānah (trust), and maslaḥah (public interest)—the decision reflects institutional responsibility and formal legality, yet leaves room for a more socially responsive approach to electoral justice. This article contributes to existing scholarship by integrating constitutional law analysis with Islamic normative values, offering an interdisciplinary perspective on electoral dispute resolution in Muslim societies. It argues that incorporating ethical and social considerations alongside procedural requirements may strengthen public trust and enhance the substantive quality of democratic governance at the local level.